Optimal operation planning of wind-hydro power systems using a MILP approach - Melício, Rui (2015)
This paper addresses an approach for a day-ahead operation of a wind-hydro power system in an electricity market. A wind-hydro system is able to mitigate the intermittence and the variations on wind power, mitigating the economic penalty due to unbalance in the satisfaction of the compromises. The approach consists in a model given by a mixed-integer linear programming. This model maximizes the profit in the day-ahead market, taking into consideration the operating constraints of both the wind the farm and the pumping-hydro system. Finally, numerical case studies illustrate the interest and effectiveness of the proposed approach.